Magnetic behavior of the novel pentagonal-bipyramidal erbium(iii) complex (Et3NH)[Er(H2DAPS)Cl2]: high-frequency EPR study and crystal-field analysis. Issue 48 (2nd December 2021) - Spillecke, Lena; Koo, Changhyun; Maximova, Olga; Mironov, Vladimir S.; Kopotkov, Vycheslav A.; Korchagin, Denis V.; Vasiliev, Alexander N.; Yagubskii, Eduard B.; Klingeler, Rüdiger
Abstract : We precisely quantified the zero field splittings of the lowest Kramers doublets for a novel Er(iii ) mononuclear complex by HF-EPR. Abstract : We report the synthesis, crystal structure and magnetic properties of the new heptacoordinated mononuclear erbium(iii ) complex (Et3 NH)[Er(H2 DAPS)Cl2 ] (H4 DAPS = 2, 6-diacetylpyridine bis-(salicylhydrazone)) (1 ). The coordination polyhedron around the Er(iii ) ion features a slightly distorted pentagonal bipyramid formed by the pentagonal N3 O2 chelate ring of the H2 DAPS ligand in the equatorial plane and two apical chloride ligands. Detailed high-frequency/high-field electron paramagnetic resonance (HF-EPR) studies of 1 result in the precise determination of the crystal field (CF) splitting energies (0, 290 and 460 GHz) and effective g -values of the three lowest Kramers doublets (KDs) of the Er(iii ) ion. The obtained HF-EPR data are in good agreement with the results from CF analysis for the Er(iii ) ion based on the simulation of the dc magnetic data of 1 . The results from dynamic susceptibility measurements indicate that there is no slow relaxation of magnetisation behaviour. This observation is discussed in terms of the electronic structure of 1 obtained from experimental and theoretical results.